ANALISIS SISTEM INFORMASI AKUNTANSI ATAS BARANG LELANG PADA PT. PEGADAIAN CABANG POMALA UNIT TANGGETADA - Hikmawati; Turi, La Ode; Ilham, Surianto (Jurnal Akuntansi Kompetif, 2025)
study aims to understand the role of accounting information systems for auction goods at PT. Pegadaian Pomala Branch. A qualitative approach was employed in this research, with data gathered through observation, interviews, and documentation. The techniques for analyzing the data include collection, reduction, and conclusion drawing. Findings from the study reveal that the accounting information system's role in managing auction goods at the PT. Pegadaian Pomala Branch Tanggetada Unit has carried out its duties well, and has proven effective in managing and calculating the selling price of auction goods. This system helps reduce credit congestion through systematic and computerized data collection, and ensures transparency and accountability in financial reports. This can be seen when a transaction occurs, it will be directly recorded by the system and must go through authorized approval. Seen from: Auction minutes, daily cash report, auction revenue money, archive documents, and documents for the auction process. Keywords: Systems, Information, Accounting